The IGSF1 Deficiency Syndrome May Present with Normal Free T4 Levels, Severe Obesity, or Premature Testicular Growth - Steven Ghanny; Aliza Zidell; Helio Pedro; Sjoerd D. Joustra; Monique Losekoot; Jan M. Wit; Javier Aisenberg (Galenos Yayincilik, 2021)
Our objective was to further expand the spectrum of clinical characteristics of the IGSF1 deficiency syndrome in affected males. These characteristic include almost universal congenital central hypothyroidism (CeH) with disharmonious pubertal development (normally timed testicular growth, but delayed rise of serum testosterone), macroorchidism, increased body mass index (BMI), and decreased attentional control. In addition, a subset of patients show prolactin deficiency, transient partial growth hormone deficiency in childhood and increased growth hormone secretion in adulthood. We present a family in which the proband was diagnosed with CeH and low serum prolactin. Severe weight gain started at two years old, with a BMI of 42.3 at 13.9 years. Testicular enlargement (5-6 mL, 3.8-4.3 standard deviation score) started aged three years. A pathogenic variant was found in the IGSF1 gene: c.3411_3412del, p.(Tyr1137*). His brother was referred for short stature at age 13 years and was diagnosed with CeH, normal serum prolactin and IGF-1, and disharmonious puberty. In four male relatives (the proband's brother and three cousins) with the variant (one adult), free thyroxine (fT4) was below the lower limit of the reference range in two, and just above this limit in the other two. Three were overweight or obese, adolescents had disharmonious pubertal development and the adult had profound macroorchidism. In conclusion, male hemizygous carriers of a pathogenic IGSF1 variant can present with fT4 concentration above the lower limit of the reference range while severe early onset obesity or premature testicular growth are part of the phenotypic spectrum.